Application of Thelearning Model Numbered Heads Togetherto Improve Student Learning Outcomes - Dewi, Dewi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
To improve student learning outcomes in the learning process, one of them is by applying the Numbered Heads Together learning model. The Numbered Heads Together learning model is a cooperative learning model that emphasizes student activities and interactions in the form of groups. By applying the Numbered Heads Together learning model, it can improve student learning outcomes that are low with the motivation and help of friends in the group. Numbered Heads Together is a cooperative learning model that stimulates student cooperation through learning in groups,students are numbered and made groups which then the teacher randomly calls the number of students and makes groups which then the teacher randomly calls the number from students so that it will create a pattern of interaction that active in the learning process